Sva. Sara Ramaṇabhāī Mahīpatarāma Nīlakaṇṭha : temanā jīvananī tathā temaṇe racelā sāhityanī māhītī āpanārā lekhono saṅgraha - Nīlakaṇṭha, Suśruta Ramaṇabhāī, 1908- (SAMP early 20th-century Indian books project ;, 1934)
On the life and works of Ramanbhai Mahipatram Nilkanth, Sir, 1868-1928, Gujarati author.